Association between economic growth, mortality and healthcare spending in 31 high-income countries. (20th October 2021) - Sanmarchi, F; Golinelli, D; Esposito, F; Toscano, F; Fantini, MP; Bucci, A
Abstract: Background: During the last decades, countries' healthcare spending has grown continuously, becoming a major expenditure item and threatening the overall sustainability of healthcare systems. Plenty of literature shows conflicting evidence about the relationship between economic variations and measurable health outcomes. This study aims to investigate the association between GDP, population mortality and healthcare spending in OECD high-income countries. Methods: We conducted a cross-sectional study using panel data across 31 high-income countries from 2000 to 2017. Socioeconomic data for every year and each country were extracted from WHO and OECD Database. The association between current healthcare expenditure (CHE), GDP and mortality rate (MR) was investigated through a random-effects model. To control for possible reverse causality, we adopted a test of Granger causality for heterogeneous panel data models. Results: The results of the random-effects model show that the MR has no statistically significant effect on CHE. We found no statistically significant association between countries' MR and GDP when the latter is the dependent variable. Our results show that an increase in GDP is associated with a significant increase of CHE (b = 0.066, p < 0.001) and CHE is significantly associated with an increase in GDP (b = 3.188, p < 0.001). The Granger causality analysis shows a unidirectional association between MR and CHE, with MR influencing CHE, albeit with a small statistical significance (p = 0.045). Between GDP and CHE, the causality is bidirectional, while between GDP and MR we found no causality. Conclusions: In this study, we found a strong two-way relationship between GDP and CHE, both in the causality analysis and in the random-effect panel model. Our analysis highlights the economic multiplier effect of CHE. In the debate on the optimal allocation of resources often resulting from economic crises, this evidence should be taken into due consideration. Key messages: Policymakers worldwide need to recognize the economic impact of healthcare spending when allocating financial resources. Spending on health leads to economic growth. In light of the current health-economy dichotomy, it is important to produce robust scientific evidence supporting healthcare spending.